Tracer study of the psychology faculty of UIN Raden Fatah Palembang in 2018: satisfaction of alumni and stakeholders on the implementation of Islamic psychology study programs - Listya Istiningtyas; Lukmawati Lukmawati (Jurnal Konseling dan Pendidikan, 2019)
As a Study Program in the new Faculty, it has produced over 400 alumni, but for ten years there has never been test the alumni side or from the stakeholder side (end user), so it is necessary to conduct research to test the satisfaction level of alumni and stakeholders. The research method used is a mixed-method with concurrent design, which uses quantitative and qualitative research. From the results of the study we can conclude it that the alumni feel quite satisfied with an average score of 3 on the three indicators; teaching and learning process, administration process and provision of facilities in Islamic Psychology Study Program, Faculty of Psychology. Therefore, it still needs to be improved in a lecture, computer and internet facilities. Islamic Psychology Study Program Faculty of Psychology has fulfilled most of the expectations of stakeholders and alumni. The advice given by stakeholders to the Faculty of Psychology to be more advance relates to improve physical facilities, human resources, services and competitiveness of graduates.